# How do you solve #4/11 x +23 = x -19#?

multiply all for 11

By signing up, you agree to our Terms of Service and Privacy Policy

Solve for x by rearranging the equation.

x = 66

Move the like terms to one side. What you do to one side of the equation is done to the other.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 4/11x + 23 = x - 19, first, subtract x from both sides to isolate the variable term. This gives: 23 = x - 4/11x - 19. Then, combine like terms by subtracting 23 from both sides: x - 4/11x = 23 - 19. Simplify: x - 4/11x = 4. Next, factor out x on the left side: x(1 - 4/11) = 4. Simplify the expression inside the parentheses: x(11/11 - 4/11) = 4. Combine like terms: x(7/11) = 4. Finally, divide both sides by 7/11: x = 4 / (7/11). Simplify: x = 4 * (11/7). Therefore, x = 44/7.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7